Health intervention research : - Sidani, Souraya (Sage, 2015)
At a time when evidence-based practice is the standard bearer for understanding health behaviour, problems and interventions, ensuring that researchers know the appropriate designs and methods for their research is more paramount than ever. Health Intervention Research will equip those doing research in these communities with the knowledge and tools they need to inform their methodological decisions when planning and conducting studies. This book describes both commonly used (e.g., randomized clinical trials) and advanced (e.g. preference trials, pragmatic trials) designs and methods for health intervention research. It outlines the theoretical reasoning underlying these different approaches, and synthesizes the evidence which supports or disputes different designs and methods. To achieve its aims, the book is divided into three main sections. The first section points to the need to base methodological decisions on evidence and highlights the importance of carefully selecting research designs and methods to maintain validity. The second section focuses on designs to determine the effects of intervention on outcomes, outlining their features and discussing how these can be used to evaluate interventions. The last section covers methods used in conducting intervention evaluation research. For each design and method, the following is covered: what it is, what the logic underlying it is, what the evidence supporting its effectiveness is, and also includes its advantages, its limitations, and how can it be implemented.